2022
DOI: 10.1186/s12864-022-08940-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genomic analyses provide new insights into the “missing” atp8 and adaptive evolution of Mytilidae

Abstract: Background Mytilidae, also known as marine mussels, are widely distributed in the oceans worldwide. Members of Mytilidae show a tremendous range of ecological adaptions, from the species distributed in freshwater to those that inhabit in deep-sea. Mitochondria play an important role in energy metabolism, which might contribute to the adaptation of Mytilidae to different environments. In addition, some bivalve species are thought to lack the mitochondrial protein-coding gene ATP synthase F0 subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 83 publications
1
9
2
Order By: Relevance
“…It was beyond the scope of this paper to suggest that further analysis might be needed to produce an affordable taxonomic revision. To our surprise, there were discrepancies between our findings and those of Zhao et al Therefore, further in-depth investigations should be conducted in the future [ 83 ].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…It was beyond the scope of this paper to suggest that further analysis might be needed to produce an affordable taxonomic revision. To our surprise, there were discrepancies between our findings and those of Zhao et al Therefore, further in-depth investigations should be conducted in the future [ 83 ].…”
Section: Discussioncontrasting
confidence: 92%
“…Combosch et al validated the monophyly of the genus Perna and indicated a misidentification in the previous study [ 81 ]. In our analysis, the Mytilisepta was clustered with P. purpuratus , as in previous studies [ 18 , 82 ], but this finding differed from the results presented by Zhao et al [ 83 ]. Moreover, Combosch et al concluded that M. virgata was most closely related to B. exustus by using a five-gene Sanger-based approach [ 81 ].…”
Section: Discussioncontrasting
confidence: 70%
“…Mitochondrial complex I is the first and largest respiratory complex required in the process of the process of oxidative phosphorylation to generate ATP, which is involved in the mitochondrial electron transport chain and is one of the major production sites of ROS (superoxide anion) ( Huang et al., 2016 ; Subrahmanian et al., 2016 ; Wang et al., 2022a ). Mutations in the members of complex I would change the metabolic capacity which may further affect adaptability of the organism ( Zhao et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The only typical metazoan protein coding gene not annotated was atp8, which is commonly absent in bivalve mitogenomes (Serb and Lydeard 2003). However, recent analyses support the presence of atp8 sequences in Pectinidae (Malkócs et al 2022) and Mytilidae (Zhao et al 2022).…”
Section: Resultsmentioning
confidence: 99%